Analysis of dialectical-based learning approach in Meno's dialogue - Mohsen Bohlooli Faskhoodi (Shahid Chamran University of Ahvaz, 2021)
IntroductionMeno's dialogue covers a wide variety of topics, including the discussion of what virtue is, the possibility of inquiry, learning, teaching methods, the relationship between knowledge and imagination, and finally the theory of recollection. Discussion of the method of teaching and learning is one of the most important topics in Meno's dialogue. In the text of this dialogue, important educational points such as the condition of teaching a subject, the method of learning based on recollection, and the dialectical method of Socrates are discussed. Conversation with Meno's paradox plan has shown that learning and inquiry the nature of something is difficult. To solve this problem, Plato spoke of the theory of recollection as to the most original way of learning. MethodThe method in this paper is philosophical-analytical based on Meno's Text and its interpretations.ResultsThe research aims to design a dialectical method in Meno's dialogue as the most appropriate method for teaching and learning critically and collaboratively in the educational system. This method is the product of cooperation between the teacher and the learner and will not be possible without the active participation of the learner and his critical attitude towards the learned material.DiscussionMeno's dialogue can be divided into two separate parts. The focus of the first part of the article is an epistemological question about understanding the nature of virtue. In the second part of the dialogue, Plato focuses on an ontological approach to get rid of the paradox of research and learning and move towards the desired result. In the final part of the dialogue, the theory of recollection. The research question is whether the theory of recollection is the best explanation for the original way of learning? Research claims that the answer is negative for two reasons. First, this theory is not able to cover any learning. Second, this theory contradicts Plato's original theory of the teaching of virtue, in which Plato claimed that any learning requires education and, consequently, a teacher.